Modeling and experimentation of multi-layered nanostructured graphene-epoxy nanocomposites for enhanced thermal and mechanical properties. (January 2017) - Atif, Rasheed; Shyha, Islam; Inam, Fawad
The influence of multi-layered nanostructured graphene as reinforcement on thermal and mechanical properties of epoxy-based nanocomposites has been studied. The maximum improvement in mechanical properties was observed at 0.1 wt%. The Young's and flexural moduli increased from 610 MPa to 766 MPa (26% increase) and 598.3 MPa to 732.8 MPa (23% increase), respectively. The tensile and flexural strengths increased from 46 MPa to 65 MPa (43% increase) and 74 MPa to 111 MPa (49% increase), respectively. The mode-1 fracture toughness (K1C ) and critical strain energy release rate (G1C ) increased from 0.85 MPa.m 1/2 to 1.2 MPa.m 1/2 (41% increase) and from 631 J/m 2 to 685 J/m 2 (9% increase), respectively. The increase in fracture toughness is attributed to the obstruction of cracks by graphene layers. The reinforcing effect of nanostructured graphene was also manifested in dynamic mechanical properties. The storage modulus and alpha-relaxation temperature values significantly increased indicating the fine integration of NSG in epoxy chains. The thermal properties of nanocomposites were simulated which showed that graphene is very efficient in significantly increasing the scattering and dissipation of thermal flux.